Siddha Ayurvedic Surgical Management of Endometrial Polyp – Case Study - Anpuchelvi, S.; Sritharan, G.; Vijitha, P. (Global Academic Research Institute Colombo, Sri Lanka, 2024)
Surgery and ovarian suppression drugs are currently the major treatments for endometriosis. Hormonal therapies are frequently linked to adverse effects, postponed conception, and disease recurrence. In the current investigation, A 48-year-old married woman with heavy monthly bleeding, brownish intermenstrual spotting that lasted for four to twelve days, and painful coitus for two years presented to the outpatient department of the Herbal Health Care Centre, Kokuvil, Jaffna, on October 20, 2021. After a thorough study found an endometrial polyp on a USG taken in 2019, she consulted a Gynecologist and started taking oral contraceptives. She advocated surgery after repeatedly taking oral contraceptive medications failed to provide any notable results. She came for Siddha Ayurvedic treatment because she rejected surgical treatment. She received Siddha treatment, and the process was recorded. In this case study, specific Siddha medicines that have the aforementioned qualities and are useful in the clinical care of endometrial Polyp were examined.
Keywords: Endometriosis; Siddha medicine; Menstrual bleeding